HUBUNGAN METODE PENGAJARAN GURU DALAM PENINGKATAN PEMAHAMAN BAHASA ARAB SISWA KELAS XI MADRASAH ALIYAH AL-IRSYAD AL-ISLAMIYYAH HAURGEULIS - Ulum, Imam Bahrul (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2023)
The Relationship of Teacher Teaching Methods in Improving Arabic Comprehension of Class XI Students of Madrasah Aliyah Al-Irsyad Al-Islamiyyah Haurgeulis. This study aims to: 1) To find out what teaching methods are used by teachers. 2) Whether there is a relationship between teaching methods and increasing students' understanding of Arabic. This study uses a quantitative approach, the number of populations in class XI was 64 with random sampling techniques, so that a sample of 55 students was obtained. This data collection technique is carried out using questionnaires, observations and documentation. The results of it can be seen that teachers use 3 types of methods, namely; lecture, discussion, and question and answer methods. Furthermore, the results of the correlation analysis test as well as hypothesis testing with non-parametric statistics using spearman rank, can be known below the significance value of 0.000 which means this value is less than 0.05 and it can be concluded that this study Ha is accepted and H0 is rejected, which means there is a relationship between teaching methods and increasing students' understanding of Arabic. Meanwhile, when viewed from the closeness of the relationship between the two variables, a correlation coefficient of 0.652 is obtained, which is in the category of a strong relationship level, or it can be said that the relationship between teaching methods and increasing students' understanding of Arabic has a strong relationship.